The syntax of small clause predication - Rafel, Joan (ZAS Papers in Linguistics, 2001)
In this paper I put forward and justify a syntactic configuration that I call Complex Small Clause-structure. I show that this single syntactic structure can explain both the semantic value and the syntactic behavior of a range of constructions that up to now have been explored separately and, hence, proposed divergent analyses among them.